2013
DOI: 10.3109/15368378.2013.831354
|View full text |Cite
|
Sign up to set email alerts
|

No genotoxic effect in exfoliated bladder cells of rat under the exposure of 1800 and 2100 MHz radio frequency radiation

Abstract: In this study, we aimed to investigate the effects of 1800 and 2100 MHz Radio Frequency (RF) radiation on the number of micronucleus (MN) in exfoliated bladder cells of rat which shows the genotoxic damage. Exposure period was 30 min/day, 6 days/week for a month and two months exposure periods. Thirty male wistar albino rats were used for five groups: Group I (n = 6): 1800 MHz RF exposed animals for one month, Group II (n = 6): 2100 MHz RF exposed animals for one month, Group III (n = 6): 2100 MHz RF exposed f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…RF field emitted from mobile phones has been mainly at frequencies 800-2000 MHz [Chen et al, 2005], which can induce adverse health effects, such as brain tumors [Morgan et al, 2015], infertility [La Vignera et al, 2012;Merhi, 2012;Sepehrimanesh et al, 2017], genotoxic effects [Atli et al, 2013;Duan et al, 2015], fatigue, rapid exhaustibility [Schoeni et al, 2015], increased anxiety, poor learning [Saikhedkar et al, 2014], and so on. Meanwhile, other studies showed beneficial effects or no effects of RF field on biological tissue [Kismali et al, 2012;Ahlers and Ammerm€ uller, 2014;Gurbuz et al, 2014]. A systematic review in 2012 [La Vignera et al, 2012] found that although RF field was discussed in a lot of published literature, not much literature described the impact of RF field produced by mobile phones on bone microstructure and metabolism, especially in-vivo experiments.…”
Section: Introductionmentioning
confidence: 99%
“…RF field emitted from mobile phones has been mainly at frequencies 800-2000 MHz [Chen et al, 2005], which can induce adverse health effects, such as brain tumors [Morgan et al, 2015], infertility [La Vignera et al, 2012;Merhi, 2012;Sepehrimanesh et al, 2017], genotoxic effects [Atli et al, 2013;Duan et al, 2015], fatigue, rapid exhaustibility [Schoeni et al, 2015], increased anxiety, poor learning [Saikhedkar et al, 2014], and so on. Meanwhile, other studies showed beneficial effects or no effects of RF field on biological tissue [Kismali et al, 2012;Ahlers and Ammerm€ uller, 2014;Gurbuz et al, 2014]. A systematic review in 2012 [La Vignera et al, 2012] found that although RF field was discussed in a lot of published literature, not much literature described the impact of RF field produced by mobile phones on bone microstructure and metabolism, especially in-vivo experiments.…”
Section: Introductionmentioning
confidence: 99%
“…The conclusions from five different experiments, employing three different concentrations of MMC, were that a) RFR exposure alone, at moderate power levels which resulted in a temperature increase in the cell culture medium of less than 3 degrees C, is not mutagenic; and b) when cells are simultaneously treated with MMC and RFR at these same moderate power levels, the RFR does not affect either the inhibition of cell growth or the extent of mutagenesis resulting from the treatment with the chemical MMC alone (51). We have two reports which show no statistically significant difference between 1800 MHz and 2100 MHz RFR exposed groups with respect to nonexposed groups (52,53).…”
Section: Radiofrequency Radiation Exposure 90mentioning
confidence: 75%
“…In a different study, it was reported that 1800 and 2100 MHz EMF radiation had no effect on exfoliated bladder cells in rats. [31] However, 3G mobile phone radiation at 2100 MHz was found to induce many histopathological changes in parotid gland of rats, but no nuclear changes were observed. [32] There are no previously published studies in the literature on the effects of a 2100 MHz EMF on fracture healing in the maxillofacial region.…”
Section: Histopathological Analysismentioning
confidence: 99%